Surgical outcome predictor analysis following hand-assisted or pure laparoscopic transperitoneal nephroureterectomy using the Taiwan upper urinary tract urothelial carcinoma database - Kuo, Chih-Chun; Chen, Guang-Heng; Chang, Chao-Hsiang; Huang, Chao-Yuan; Chen, Chung-Hsin; Li, Ching-Chia; Wu, Wen-Jeng; Yu, Chih-Chin; Lo, Chi-Wen; Chen, Yung-Tai; Chen, Shin-Hong; Cheng, Pai-Yu; et al. (Frontiers in Surgery, 2022)
Purpose: Taiwan has a high incidence of upper tract urothelial carcinoma (UTUC). This study aimed to compare surgical outcomes following transperitoneal hand-assisted laparoscopic nephroureterectomy (TP-HALNU) and transperitoneal pure laparoscopic nephroureterectomy (TP-LNU) from the Taiwan nationwide UTUC collaboration database using different parameters, including surgical volumes. Materials and Methods: The nationwide UTUC collaboration database includes 14 hospitals in Taiwan from the Taiwan Cancer Registry. We retrospectively reviewed the records of 622 patients who underwent laparoscopic nephroureterectomy between July 1988 and September 2020. In total, 322 patients who received TP-LNU or TP-HALNU were included in the final analysis. Clinical and pathological data and oncological outcomes were compared. Results: Of the 322 patients, 181 and 141 received TP-LNU and TP-HALNU, respectively. There were no differences in clinical and histopathological data between the two groups. No differences were observed in perioperative and postoperative complications. There were no significant differences in oncological outcomes between the two surgical approaches. In the multivariate analysis, the cohort showed age > 70 years, positive pathological lymph node metastasis, tumors located in the upper ureter, and male sex were predictive factors associated with an increased risk of adverse oncological outcomes. A surgical volume of >20 cases showed a trend toward favorable outcomes on cancer-specific survival (hazard ratio [HR] 0.154, p=0.052) and marginal benefit for overall survival (HR 0.326, p=0.019) in the multivariate analysis. Conclusion: Although different approaches to transperitoneal laparoscopic nephroureterectomy showed no significant differences in surgical outcomes, age, sex, lymph node metastasis, and tumor in the upper ureter in the following period were predictive factors for oncological outcomes. Higher surgical volume did not impact disease-free survival and bladder recurrence-free survival but was associated with improved overall survival and cancer-specific survival. Exploration of unknown influencing factors is warranted.